Revisiting the role of neurons in neurovascular coupling - Cauli, Bruno; Hamel, Edith (Frontiers in Neuroenergetics, 2010)
In this article, we will review molecular, anatomical, physiological and pharmacological data in an attempt to better understand how excitatory and inhibitory neurons recruited by distinct afferent inputs to the cerebral cortex contribute to the coupled hemodynamic response, and how astrocytes can act as intermediaries to these neuronal populations. We aim at providing the pros and cons to the following statements that, depending on the nature of the afferent input to the neocortex, (i) different neuronal or astroglial messengers, likely acting in sequence, mediate the hemodynamic changes, (ii) some recruited neurons release messengers that directly alter blood vessel tone, (iii) others act by modulating neuronal and astroglial activity, and (iv) astrocytes act as intermediaries for both excitatory and inhibitory neurotransmitters. We will stress that a given afferent signal activates a precise neuronal circuitry that determines the mediators of the hemodynamic response as well as the level of interaction with surrounding astrocytes.